ARC discharge in a cross flow of gas - Chernyak, V.Ya.; Naumov, V.V.; Yukhymenko, V.V.; Babich, I.L.; Zrazhevskyy, V.A.; Woewoda, Yu.V.; Pashko, T.V. (Вопросы атомной науки и техники, 2005)
The experimental study of nonequilibrium air plasma flow of atmospheric pressure in the transverse arc discharge of high voltage is conducted. The high non-izothemality in the air plasma during its space evolution is shown in dependence on the gas flow rate and discharge energy deposition with a detailed emission spectroscopic diagnostics of excited atoms, molecules and radicals along the plasma jet.